Assessment of Diffuse Ventricular Myocardial Fibrosis Using Native T1 in Children With Repaired Tetralogy of Fallot. (March 2017) - Yim, Deane; Riesenkampff, Eugenie; Caro-Dominguez, Pablo; Yoo, Shi-Joon; Seed, Mike; Grosse-Wortmann, Lars
Abstract : Background—: Myocardial fibrosis is linked with adverse clinical outcomes in adults after tetralogy of Fallot repair (rTOF). Native T1 times (T1) by cardiac magnetic resonance have been shown to be a surrogate marker of diffuse myocardial fibrosis. The objective was to quantify native T1 in children post-rTOF and to evaluate their relationship with surgical, imaging, and clinical factors. Methods and Results—: A retrospective cross-sectional study was performed. Midventricular native T1 were obtained in 100 children post-rTOF using a modified look-locker inversion recovery cardiac magnetic resonance sequence and compared with 35 pediatric controls. rTOF patients, aged 13.0±2.9 years, had higher indexed right ventricular (RV) end-diastolic (range 85–326 mL/m 2, mean 148 mL/m 2 ) volumes, and lower RV and left ventricular (LV) ejection fractions compared with controls. RV, but not LV, T1 were higher in patients than in controls (1031±74 versus 954±32 ms, P <0.001) and female patients had higher RV T1 compared with males (1051±79 versus 1017±68 ms, P =0.02). LV T1 correlated with RV T1 ( r =0.45, P <0.001), cardiopulmonary bypass ( r =0.30, P =0.007), and aortic cross-clamp times ( r =0.32, P =0.004). RV T1 correlated inversely with RV outflow tract gradient ( r =-0.28, P =0.02). Longer aortic cross-clamp times were independently associated with LV and RV T1 on multivariable analysis. There was no association between exercise intolerance, arrhythmia, and native T1 or LV extracellular volume. Conclusions—: Children after rTOF do not have elevated LV native T1 or LV extracellular volume, but show evidence of increased RV native T1 suggestive of diffuse RV fibrosis, for which volume loading seems to be a risk factor. Surgical bypass and cross-clamp times are associated with fibrotic remodeling over a decade later.